Photomethanation of Gaseous CO2 over Ru/Silicon Nanowire Catalysts with Visible and Near‐Infrared Photons. (25th November 2014) - O'Brien, Paul G.; Sandhel, Amit; Wood, Thomas E.; Jelle, Abdinoor A.; Hoch, Laura B.; Perovic, Doug D.; Mims, Charles A.; Ozin, Geoffrey A.
<x xml:space="preserve">Abstract</x> Gaseous CO2 is transformed photochemically and thermochemically in the presence of H2 to CH4 at millimole per hour per gram of catalyst conversion rates, using visible and near‐infrared photons. The catalyst used to drive this reaction comprises black silicon nanowire supported ruthenium. These results represent a step towards engineering broadband solar fuels tandem photothermal reactors that enable a three‐step process involving i) CO2 capture, ii) gaseous water splitting into H2, and iii) reduction of gaseous CO2 by H2. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>